Problems of introducing the GTO complex in higher education institutions - S.Yu. Shchetinina, (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the problems of introducing the GTO complex in universities and identify measures that increase the motivation of students and university staff to comply with the standards of the GTO complex. Methods and structure of the study. In the period of 2018-2023 academic year, sociological surveys were conducted among students of the Pacific State University (PNU) on various aspects of the GTO and their attitude to the complex. Results and conclusions. The practice of introducing the GTO complex in universities, a survey of students showed that many students are not interested in its implementation; causes are indicated. The results of student surveys on various aspects of the GTO and their attitude to the complex are presented; factors contributing to the motivation of students to pass the standards of the GTO complex were identified. The low activity of university employees in fulfilling the standards of the GTO complex is indicated. The issues of the need to strengthen the incentive system for students and employees for participating in competitions and meeting standards are considered. A set of measures has been outlined to encourage students and university staff to participate in passing the standards of the GTO complex, which will help improve the situation with its implementation in universities.